The Effect of Supervision, Compensation, Character on Work Discipline - Hajiali, Ismail; Fara Kessi, Andi Muhammad; Budiandriani, B.; Prihatin, Etik; Sufri, Mukhlis (Golden Ratio of Human Resource Management, 2022)
This study comprehensively examines the relationship between the variables Supervision, Compensation, Character on Work Discipline. The study was conducted for 3 months at PT. PLN Makassar City with a total sample of 30 respondents from employees of PT. PLN. The data analysis method used multiple linear regression. The results of the study stated that Supervision has a significant effect on Work Discipline. This can be seen from the results of the t-test with a t-value of 0.767 smaller than t-estimated 1.687 and a significant (H1 is accepted). Compensation has a significant effect on employee with the t value of 1.354 smaller than the t table of 1.687 and a significant value of < 0.001 (H2 is accepted). Character does not have a significant effect on Work Discipline. This can be seen from the results of the t-test on the monitoring variable with the t-value of 0.128 smaller than the t-estimated of 0.900 and a significant value of 0.900 (H3 is not accepted). This study suggest to improve the quality of supervision to employees and provide better supervision by providing tighter and maximum regulations so that automatically the symptoms of irregularities or errors can be prevented and will increase work discipline.